2004
DOI: 10.1002/cne.11044
|View full text |Cite
|
Sign up to set email alerts
|

OL‐protocadherin expression in the visual system of the chicken embryo

Abstract: The expression of OL-protocadherin, a homotypically binding cell adhesion molecule, was mapped in the visual system of the chicken embryo at intermediate to late stages of development (11-19 days of incubation). The expression was compared with that of four classic cadherins, described previously. OL-protocadherin is expressed by the isthmooptic nucleus, its retinopetal projection, and possibly its retinal target neurons, the amacrine cells. Ganglion cells begin to express OL-protocadherin at relatively late s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…In the vertebrate brain, Pcdh10 is expressed in neural circuits of several functional systems (Hirano et al, 1999;Müller et al, 2004). Our results confirm findings by Nakao et al (2005).…”
Section: Pcdh10supporting
confidence: 94%
See 1 more Smart Citation
“…In the vertebrate brain, Pcdh10 is expressed in neural circuits of several functional systems (Hirano et al, 1999;Müller et al, 2004). Our results confirm findings by Nakao et al (2005).…”
Section: Pcdh10supporting
confidence: 94%
“…In addition, the following plasmids were used for probe synthesis: OL-protocadherin (nucleotides 70-352 and 2,259-3,899 from the cDNA of chicken Pcdh10; Genbank accession no. AF334802; Müller et al, 2004;Nakao et al, 2005; gift of Dr. S. Hirano, RIKEN for Developmental Biology, Kobe, Japan); Cadherin-7 (full-length sequence of Cdh7, Genbank accession no. NM_204187.2; Nakagawa and Takeichi, 1995; gift of Drs.…”
Section: Cloning Of Cdna Fragments Of Delta-pcdhsmentioning
confidence: 99%
“…Two recent studies also supported this hypothesis for amphibians (Milán and Puelles, 2000;Morona and González, 2008), and substantial evidence has been reported for amniote tetrapods (Martínez-de-la-Torre, 1985;Medina et al, 1992Medina et al, , 1993Puelles, 1995Puelles, , 2001Redies et al, 1997Redies et al, , 2000De Castro et al, 1998;Dávila et al, 2000;Martínez and Puelles, 2000;Yoon et al, 2000;GarciaCalero et al, 2002;Puelles and Rubenstein, 2003;Müller et al, 2004;García-López et al, 2004;Ferran et al, 2007Ferran et al, , 2009). Thus, the data presented here confirm the suggested subdivisions in amphibians (Puelles et al 1996;Milán and Puelles, 2000;Morona and González, 2008) and corroborate the model proposed for amniotes (Ferran et al, 2007(Ferran et al, , 2008.…”
Section: Anteroposterior Subdivisionsmentioning
confidence: 72%
“…protocadherin 10 (PCDH10/OL-PCDH/KIAA1400) is a nonclustered-type protocadherin with a unique cytoplasmic domain [5]. It is reported that there is a correlation between the expression pattern of PCDH10 and functional systems of the brain such as the visual and limbic systems [6][7][8]. Unlike other protocadherin family members, PCDH10 was discovered to have widespread expression [9].…”
mentioning
confidence: 99%